Surface characterization of mechanically activated sulphides. (4th August 2014) - Balaz, Peter; Eva, Bastl; Moser, M.; Roths, Manfred
The effect of mechanical activation on the surface properties of zinc, lead (II) and antimony (III) sulphides produced by dry intensive grinding in a vibration mill and a planetary mill was studied by ESCA and IR methods. It was found that favourable conditions for mechanochemical transformations including formation of variable surface species were created by grinding.